Corrosion behaviour of Q235B carbon steel in sediment water from crude oil. (October 2016) - Cheng, Qingli; Tao, Bin; Song, Liying; Zhang, Weihua; Liu, Xiuyun; Li, Weihua; Hou, Baorong; Liu, Quanzhen
Highlights: The surface of carbon steel was mainly covered with CaCO3 deposits. The corrosion rate decreased during the first 5 weeks of immersion. The corrosion rate increased after the 5 weeks of immersion. The corrosion system was intensely localized. Corrosion preferentially occurred under the CaCO3 deposits. Abstract: The effects of sediment water from crude oil on Q235B carbon steel corrosion were investigated through electrochemical measurements, surface characterization, mass loss, and mass gain techniques for 11 weeks of immersion. Results showed that the steel surfaces were covered by scale deposits consisting mainly of CaCO3 . Corrosion pits were initiated under the scale deposits. Moreover, a galvanic corrosion cell was generated under the scale deposits, resulting in localized dissolution. However, the scale deposits blocked the transport of corrosion products into the bulk solution, thereby causing the accumulation of corrosion products under the scale deposits.